1995
DOI: 10.1177/00220345950740111001
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Fluoride in Carious Human Enamel

Abstract: The proton probe has been used to map F concentration changes in the enamel of 15 teeth showing clinical evidence of caries. Thin sections through the lesions were microradiographed and measurements made of the surface zone (radiodense) and body (radiolucent) areas. Each section was then scanned with a focused beam of 2.5 MeV protons, 2000 spot analyses being performed over areas up to 2 x 3 mm. F was determined by detecting gamma rays from a nuclear reaction and the data used to construct 3-D surface plots. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
2
10
0
1
Order By: Relevance
“…We found that the fluoride concentration in the surface and subsurface regions was two to four times higher (Table 3) respectively, which supports the concept that fluoride-rich mineral coat the intraprismatic spaces in remineralized lesions. These results agree with reports of higher acid resistance and fluoride content in arrested enamel caries than in sound enamel, [23][24][25] and is probably one reason why the laminar pattern underneath the remineralized lesions was more pronounced in the FCG group after the acid challenge (Fig 4). This laminar pattern was present in some of the control group because the original enamel probably contained high fluoride levels.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the fluoride concentration in the surface and subsurface regions was two to four times higher (Table 3) respectively, which supports the concept that fluoride-rich mineral coat the intraprismatic spaces in remineralized lesions. These results agree with reports of higher acid resistance and fluoride content in arrested enamel caries than in sound enamel, [23][24][25] and is probably one reason why the laminar pattern underneath the remineralized lesions was more pronounced in the FCG group after the acid challenge (Fig 4). This laminar pattern was present in some of the control group because the original enamel probably contained high fluoride levels.…”
Section: Discussionsupporting
confidence: 92%
“…there was a high concentration of F in a layer at the surface, declining steeply to a low and relatively constant F level in the enamel interior [Nakagaki et al, 1987;Pearce et al, 1995;Cutress et al, 1996]. Along this narrow band the groove/fissure F concentration fluctuated as it does in sound outer smooth surface enamel [Pearce et al, 1995] but not because of abrasion, a factor known to reduce surface F in unprotected areas [Weatherell et al, 1983].…”
Section: Discussionmentioning
confidence: 97%
“…there was a high concentration of F in a layer at the surface, declining steeply to a low and relatively constant F level in the enamel interior [Nakagaki et al, 1987;Pearce et al, 1995;Cutress et al, 1996]. Along this narrow band the groove/fissure F concentration fluctuated as it does in sound outer smooth surface enamel [Pearce et al, 1995] but not because of abrasion, a factor known to reduce surface F in unprotected areas [Weatherell et al, 1983]. The fluctuations in this sound fissure enamel could be a developmental effect, or the result of uneven post-eruptive uptake of topical F. In the only narrow fissure where measurements could be made, the high F surface layers on both sides appeared to be somewhat narrower near the fissure bottom and gradually widened towards the fissure opening ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 50 years, fluoride has been claimed to be effective in preventing the caries process through inhibiting demineralization and increasing remineralization by forming fluorapatite and calcium fluoride as well as inhibiting the work of bacterial enzymes through antimicrobial activities (Kirkham et al, 1994;Torgay et al, 1994;Pearce et al, 1995;Cury and Tenuta, 2009 Research, 2000). Recent consensus claims that fluoride is no longer used systemically but rather used locally through direct application on the teeth (Cury and Tenuta, 2008).…”
Section: Introductionmentioning
confidence: 99%